Horizontal gene transfer via OMVs co-carrying virulence and antimicrobial-resistant genes is a novel way for the dissemination of carbapenem-resistant hypervirulent Klebsiella pneumoniae - Li, Ping; Luo, Wanying; Xiang, Tian-Xin; Jiang, Yuhuan; Liu, Peng; Wei, Dan-Dan; Fan, Linping; Huang, Shanshan; Liao, Wenjian; Liu, Yang; Zhang, Wei (Frontiers in Microbiology, 2022)
Introduction The rapidly increased isolation rate of CR-HvKP worldwide has brought great difficulties in controlling clinical infection. Moreover, it has been demonstrated that the transmission of drug-resistant genes among bacteria can be mediated by outer membrane vesicles (OMVs), which is a new way of horizontal gene transfer (HGT). The transmission of virulence genes among bacteria has also been well studied; however, it remains unclear whether virulence and drug-resistant genes can be co-transmitted simultaneously. Co-transmission of virulence and drug-resistant genes is essential for the formation and prevalence of CR-HvKP. Methods First, we isolated OMVs from CR-HvKP by cushioned-density gradient ultracentrifugation (C-DGUC). TEM and DLS were used to examine the morphology and size of bacterial OMVs. OMV-mediated gene transfer in liquid cultures and the acquisition of the carbapenem gene and virulence gene was confirmed using colony-PCR. Antimicrobial susceptibility testing, mCIM and eCIM were conducted for the resistance of transformant. Serum killing assay, assessment of the anti-biofilm effect and galleria mellonella infection model, mucoviscosity assay, extraction and quantification of capsules were verified the virulence of transformant. Pulsed-field gel electrophoresis (PFGE), S1 nuclease-pulsed-field gel electrophoresis (S1-PFGE), Southern blotting hybridization confirmed the plasmid of transformant. Results Firstly, OMVs were isolated from CR-HvKP NUHL30457 (K2, ST86). TEM and DLS analyses revealed the spherical morphology of the vesicles. Secondly, our study demonstrated that CR-HvKP delivered genetic material, incorporated DNA within the OMVs, and protected it from degradation by extracellular exonucleases. Thirdly, the vesicular lumen DNA was delivered to the recipient cells after determining the presence of virulence and carbapenem-resistant genes in the CR-HvKP OMVs. Importantly, S1-PFGE and Southern hybridization analysis of the 700603 transformant strain showed that the transformant contained both drug-resistant and virulence plasmids. Discussion In the present study, we aimed to clarify the role of CRHvKP-OMVs in transmitting CR-HvKP among K. pneumoniae. Collectively, our findings provided valuable insights into the evolution of CR-HvKP.